Too tired to fight : 13 essential conflicts parents must have to keep their relationship strong - Mitchell, Erin (Counseling psychologist) (G.P. Putnam's Sons, 2024)
"Decode the 13 conflicts that derail many couples' communication after kids--like what you're really saying when you fight about discipline or diapers, and how to work through tough issues together--from popular Instagram counselors Erin Mitchell, MACP, and Stephen Mitchell, PhD"--